A new anti-freezing foam scrubbing agent technology research. (August 2019) - Zhang, Guangsheng; Duan, Qiong; Cao, Feng; Sun, Ning
Abstract: With the long delaying development and the higher pressure, the anniversary production of Yu-Lin Gas Field is reducing. Because of the lower temperature in the winter, the traditional foam scrubbing agent is not easy to foam that makes a poor drainage effect, lower developing and decreasing benefits. According to the common anti-freezer properties and parts of some development data, new anti-freezing foam scrubbing agent laboratory experimental study was put forward. Computed with the water production, when the new foam agent consumption is 200-400g/L, the roaming ration, foam stability and water carrying ability is greatly improved. When the foam agent consumption is 200g/L, the freezing point of foam scrubbing agent can reach to-10°C, and when 400g/L, it can reach to -25°C, which both satisfy the site temperature condition.